A comparative economic analysis of conventional and modified Solvay processes vs. solar ponds for brine management - Dina Ewis (14149998) (2025)
This study conducts a comprehensive economic comparison between the conventional and Ca(OH)₂-modified Solvay processes and solar ponds as brine management technologies. In this context, the Solvay process presents a dual advantage by producing sodium bicarbonate, an economically valuable compound while simultaneously mitigating two critical environmental challenges: CO₂ emissions and brine waste. The analysis considers various brine characteristics, including temperature, pressure, and salinity, to assess their impact on the process's economic feasibility. In addition, the model evaluates CO2 and sodium removal, as well as the associated economics, for different water salinities, including brackish water, seawater, and reject brine. Also, the economic profitability of the Solar Pond under similar reject brine characteristics was investigated. The results suggest that Ca(OH)2 modified Solvay is applicable for all types of water salinities ranging between 5 and 90 PSU with associated profit ranging from 0.5 $/m3 to 9 $/m3. Whereas Solar Pond requires expenses of 6 $/m3 of brine under the current used Solar Pond efficiencies (ORC 3.25 % and electricity price of 0.15 $/kWh). Overall, modified Solvay process not only generates profit but also simultaneously mitigates CO₂ emissions and reduces reject brine salinity significantly compared to Conventional Solvay. On the other hand, the solar pond process only reduces brine salinity without fully removing the residual salts, which still require costly landfill disposal, and overall, the process fails to generate profit under current efficiency conditions. Therefore, implementing the modified Solvay process offers the dual benefits of economic profitability and environmental sustainability. Other Information Published in: Desalination License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.desal.2025.119119